Penerapan Metode Simpleks Untuk Optimasi Produksi pada UMKM Syifa Hidroponik Medan - Qori Aulia Hafni Nasution; Fara Syifa Nabila Siregar; Annisa Aulia Dahlan Dalimunthe; Asrah Nabila Purba; Siti Salamah Br. Ginting (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to optimize the production process of kale-based food preparations, namely kale rendang and kale arsik, using a linear program approach. The main problem faced by business actors is limited resources such as raw materials, production time, and work capacity. By utilizing the simplex method, this study formulates a mathematical model of the objective function and real constraints in the production process. The optimization results show that to obtain maximum profit of Rp 3,000,000 per production cycle, the best strategy is to produce two units of kale rendang without producing kale arsik. This analysis confirms that kangkung rendang is mathematically more profitable than kangkung arsik, under the existing constraints. The findings recommend the use of linear programs as an effective decision-making tool in the planning and management of local food-based MSME production.